2019
DOI: 10.1186/s12866-019-1640-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of theophylline via aerobic fermentation of pu-erh tea using tea-derived fungi

Abstract: BackgroundCaffeine is one of the most abundant methylxanthines in tea, and it remains stable in processing of general teas. In the secondary metabolism of microorganism, theophylline is the main conversion product in caffeine catabolism through demethylation. Microorganisms, involved in the solid-state fermentation of pu-erh tea, have a certain impact on caffeine level. Inoculating an appropriate starter strain that is able to convert caffeine to theophylline would be an alternative way to obtain theophylline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
0
32
1
1
Order By: Relevance
“…We found that theophylline content was increased significantly (p < 0.05) and Aspergillus sydowii caused caffeine degradation in SSF [40]. After further research, A. sydowii had a significant (p < 0.05) impact on caffeine metabolism and potential value in theophylline production through aerobic fermentation [41,42].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…We found that theophylline content was increased significantly (p < 0.05) and Aspergillus sydowii caused caffeine degradation in SSF [40]. After further research, A. sydowii had a significant (p < 0.05) impact on caffeine metabolism and potential value in theophylline production through aerobic fermentation [41,42].…”
Section: Introductionmentioning
confidence: 74%
“…The colony forming units (CFU) were calculated by per gram of the dry weight after 2 days of cultivation at 30 °C. Caffeine and theophylline contents were determined by HPLC described by Zhou et al [40,41] using an Agilent 1200 series system and an Agilent C 18 Chromatogram column (250 mm × 4.6 mm, 5 μm). Samples collected on days 20 and 25 were stored at 4 °C and selected for further isolation and identification of theophylline-degrading fungi.…”
Section: Pu-erh Tea Solid-state Fermentation and Determination Of Cafmentioning
confidence: 99%
See 3 more Smart Citations